2014
DOI: 10.1002/dta.1769
|View full text |Cite
|
Sign up to set email alerts
|

Annual banned‐substance review: analytical approaches in human sports drug testing

Abstract: Within the mosaic display of international anti-doping efforts, analytical strategies based on up-to-date instrumentation as well as most recent information about physiology, pharmacology, metabolism, etc., of prohibited substances and methods of doping are indispensable. The continuous emergence of new chemical entities and the identification of arguably beneficial effects of established or even obsolete drugs on endurance, strength, and regeneration, necessitate frequent and adequate adaptations of sports dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 192 publications
0
11
0
Order By: Relevance
“…Most methods of androgen monitoring rely on detecting, by MS, the chemical signature of T and known AAS within the urine of the athlete [ 14 17 ]. Since chemical assessment relies on a prior knowledge of the AASs, novel methods are currently under consideration that detect AAS activity in an athlete’s bodily fluids, even if the AAS is unknown [ 5 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most methods of androgen monitoring rely on detecting, by MS, the chemical signature of T and known AAS within the urine of the athlete [ 14 17 ]. Since chemical assessment relies on a prior knowledge of the AASs, novel methods are currently under consideration that detect AAS activity in an athlete’s bodily fluids, even if the AAS is unknown [ 5 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure and Table S5, an extraction time of 1 min from 700 μL of urine was sufficient to achieve LOQs ranging between 100 and 500 pg mL –1 . Not only were LOQ values below MRPL levels (i.e., 50–100 ng mL –1 ), , but also rewarding correlation coefficients (>0.999) were observed for all probes in the range evaluated (i.e., 100 pg mL –1 up to 500 ng mL –1 ; see Figures and S4). Since SPME derives its sensitivity and selectivity from the physicochemical/geometrical characteristics of the coating used, current research is directed toward the development of thinner coatings with greater affinity for the target analytes (e.g., HLB), with aims to provide lower limits of detection without compromising total analysis time .…”
Section: Resultsmentioning
confidence: 91%
“…Due to its noninvasive sample collection nature and the typically large sample volumes available, urine is the most traditional matrix employed when monitoring abuse of illicit drugs or doping in sports . Since the amount of parent drug excreted in urine is typically low (e.g., parent drug could be metabolized by the liver), analytical methods capable of providing sensitive analysis in the subnanogram per milliliter levels are needed. , Recently, Boyacı et al and Reyes-Garcés et al , demonstrated that different geometrical formats of SPME were capable of meeting the minimum required performance levels (MRPL) set by the World Anti-Doping Agency (WADA) for the analysis of prohibited substances in urine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports performance enhancement: Professional and amateur athletes are targeted with designer anabolic steroids and stimulants, many of which are banned by the World Anti‐Doping Agency (WADA) 19. Functional and structural diversity, synthetic proclivity of the adulterators, and the generally small amounts of the infringing substances required to elicit a therapeutic effect make this category especially challenging to address.…”
Section: Dietary Supplements Health and Education Act (Dshea) Good Mmentioning
confidence: 99%